Deceitfulness and Avidity In Education-A Study of Selected Academic Novels: Unmasking the Truth: Examining Deceitfulness and Avidity in Education through Academic Novels (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Tracingthe conflicts, the desires, the Deceitfulness and hypocrisies inherent in theuniversity set up, the thesis demonstrates that individuals within the academeare m no way different from those outside the academe. They try to put on a maskthat everything is fine but the writers of academic novels are engaged in thetask of tearing this mask and portraying the insider's real experience andperception. Thethesis is divided into eight chapters and the introduction gives a briefcritical survey of the American academic novel and of academic novels fromvarious other regions of the world It tries to show the differences in theattitude of various writers of academic novels While certain novelists areengaged in depicting the plight of professors, some others are keen on showingthe students' problems, yet others deal with the problems on the administrativeside But whatever may be the area of study, these writers are keen on assessingthe flaws in the University They cannot leave it, because it is the arena fromwhich they can speak. Finally the thesis projects the view that though theacademicians have their defects yet we should allow room for the fact that theytoo are individuals and they too are liable to make mistakes. That is why writerslike John Barth resort to black humor to point out the mistakes of those withinthe university. Indirectly he wants reform our universities and colleges and hehas to a certain extent made individuals think about their role in forming ouruniversities. He has kindled us to think, but the outcome is very difficult toassess.